ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK PADA PIDATO PRESIDEN DI KTT KE-42 ASEAN - SYAFRI BIN SAKKA; NURHADI NURHADI; ESTI SWASTIKA SARI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2023)
This study aims to provide an explanation in a text that is studied by a person or group with the aim of disclosing the interests of certain parties. The method used in this study is a qualitative descriptive method with analysis of crisis discourse by Teun A. Van Djik. The Van Djik model of critical discourse analysis is divided into three dimensions, namely the text dimension, the social cognition dimension, and the social context dimension. The results of the research show that the dimensions of the text in the critical discourse analysis model of Teun A. Van Djik are divided into macro structures, super structures and micro structures. In each discourse structure, there are several elements found in the discourse of the president's speech at the 42nd ASEAN Summit. The macro structure is found in the topic/theme elements contained in the president's speech. In the super structure, schema elements are found in the form of a series of opinions that are arranged and arranged, such as introduction, content, and closing. Micro structure is divided into semantics, syntax, stylistics, and rhetoric. Semantic elements include background and detail elements, while syntax includes sentence forms, coherence, and pronouns. Stylistic elements are found in lexicon or word selection, while rhetorical elements are only found in expression elements. Social cognition is influenced by three elements, namely knowledge, opinion and attitude, and the last is ideology. The social context dimension was found to influence the discourse of the president's speech at the 42nd ASEAN Summit which was reinforced by news quotes from newspapers and other media. ABSTRAKPenelitian ini bertujuan untuk memberi penjelasan dalam teks yang dikaji oleh seseorang atau kelompok yang memiliki tujuan untuk mengungkap kepentingan dari pihak tertentu. Metode yang digunaka pada penelitian ini adalah metode deskriptif kualitatif dengan analisis wacana krisis oleh Teun A. Van Djik. Analisis wacana kristis model Van Djik terbagi atas tiga dimensi yaitu dimensi teks, dimensi kognisi sosial, dan dimensi konteks sosial. Hasil dari penelitian menunjukkan Dimensi teks pada analisis wacana kritis model Teun A. Van djik terbagi atas Struktur makro, super struktur, dan struktur micro. Setiap struktur wacana terdapat beberapa elemen yang ditemukan pada wacana pidato presiden di KTT ke 42 ASEAN. Struktur makro ditemukan elemen topik/tema yang terdapat pada pidato presiden. Super struktur ditemukan elemen skema berupa rangkaian pendapat yang disusun dan dirangkai, seperti pendahuluan, isi, dan penutup. Struktur micro terbagi atas semantik, sintaksis, stilistik, dan retoris. Elemen semantik terdapat unsur latar dan detil, sintaksis terdapat unsur bentuk kalimat, koherensi, dan kata ganti. Elemen stilistik terdapat unsur leksikon atau pemilihan kata, sedangkan elemen retoris hanya ditemukan unsur ekspresi. Kognisi sosial dipengaruhi oleh tiga elemen yaitu pengetahuan, opini dan sikap, dan yang terakhir adalah ideologi. Dimensi konteks sosial ditemukan pengaruh wacana pidato presiden di KTT ke 42 ASEAN yang dikuatkan oleh kutipan berita dari surat kabar dan media lainnya.